Awake tracheotomy in a patient with stridor and dyspnoea caused by a sizeable malignant thyroid tumor: a case report and short review of the literature. Issue 11 (5th October 2017) - Hohn, Andreas; Kauliņš, Tālis; Hinkelbein, Jochen; Kauliņa, Krista; Kopp, Andreas; Russo, Sebastian G.; Kohlen, Sigurd; Schröder, Stefan
Key Clinical Message: Individual airway management is mandatory in patients with large goiters undergoing thyroid surgery. Preoperative endoscopic airway evaluation and imaging studies can support clinical decision making. Awake tracheotomy can be an effective and reasonable airway management strategy in such patients. Abstract : Individual airway management is mandatory in patients with large goiters undergoing thyroid surgery. Preoperative endoscopic airway evaluation and imaging studies can support clinical decision making. Awake tracheotomy can be an effective and reasonable airway management strategy in such patients.